Carbohydrate supplementation during exercise: Does it help? How much is too much? - Jeukendrup, A. (Sports Science Exchange, 2007)
KEY POINTS - Carbohydrate intake during exercise can delay the onset of fatigue and improve performance of prolonged exercise as well as exercise of shorter duration and greater intensity (e.g., continuous exercise lasting about 1 h and intermittent high-intensity exercise), but the mechanisms by which performance is improved are different. - During prolonged exercise, the performance benefi ts of carbohydrate ingestion are likely achieved by maintaining or raising plasma glucose concentrations and sustaining high rates of carbohydrate oxidation, whereas durin intense exercise, carbohydrate intake seems to positively affect the central nervous system. - Carbohydrate from a single source, such as glucose, can only be oxidized at rates of approximately 60 g/h. - When a combination of carbohydrates is ingested (e.g., glucose and fructose) oxidation rates of slightly more than 100 g/h can be achieved if large amounts of carbohydrate are ingested (e.g., > 140 g/h). - Ingesting a carbohydrate solution that is very concentrated and/or has a high osmolality is likely to cause gastrointestinal discomfort. - The amount of carbohydrate an individual athlete should ingest during exercise should be determined by trial and error, and a balance should be struck between increasing carbohydrate availability during exercise and minimizing gastrointestinal distress.